2022
DOI: 10.1186/s13041-022-00969-w
|View full text |Cite
|
Sign up to set email alerts
|

The role of triggering receptor expressed on myeloid cells-1 (TREM-1) in central nervous system diseases

Abstract: Triggering receptor expressed on myeloid cells-1 (TREM-1) is a member of the immunoglobulin superfamily and is mainly expressed on the surface of myeloid cells such as monocytes, macrophages, and neutrophils. It plays an important role in the triggering and amplification of inflammatory responses, and it is involved in the development of various infectious and non-infectious diseases, autoimmune diseases, and cancers. In recent years, TREM-1 has also been found to participate in the pathological processes of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 138 publications
0
7
0
Order By: Relevance
“…Of potential relevance to age-related loss of motor synapses, the translatomes of both aged female and male motor neurons are enriched for genes with roles in the complement system and TREM1 signaling ( Figure 8H ). Both complement signaling ( 62 66 ) and TREM1 ( 67 , 68 ) have been shown to mediate synaptic pruning by microglia; thus, motor neurons undergo molecular changes during aging that may cause microglia to target motor synapses.…”
Section: Resultsmentioning
confidence: 99%
“…Of potential relevance to age-related loss of motor synapses, the translatomes of both aged female and male motor neurons are enriched for genes with roles in the complement system and TREM1 signaling ( Figure 8H ). Both complement signaling ( 62 66 ) and TREM1 ( 67 , 68 ) have been shown to mediate synaptic pruning by microglia; thus, motor neurons undergo molecular changes during aging that may cause microglia to target motor synapses.…”
Section: Resultsmentioning
confidence: 99%
“…mTREM-1 is a type I transmembrane glycoprotein receptor composed of an extracellular immunoglobulin domain, a transmembrane region, and a cytoplasmic domain ( 49 ). The extracellular domain is primarily responsible for ligand binding, while the transmembrane region associates with the DNAX-activating protein 12 (DAP12) adapter protein through non-covalent bonds, transmitting signals within the cell ( 50 ). sTREM-1 is a glycosylated peptide with only one immunoglobulin-like domain.…”
Section: Overview Of the Trem Familymentioning
confidence: 99%
“…Little is known about the ligands that activate TREM1. Limited evidence suggested that high mobility group box 1 (HMGB1), PGN recognition protein 1 (PGLYRP1), heat shock protein 70 (HSP70), CD177, actin, and extracellular cold-inducible RNA-binding protein (eCIRP) may be ligands for TREM-1 ( 50 , 54 , 55 ).…”
Section: Overview Of the Trem Familymentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophages are important immune cells in the body and play a key role in chronic inflammation in many lung diseases ( 9 ). Triggering receptor expressed on myeloid cells-1 (TREM-1), a member of the immunoglobulin superfamily, is largely enriched on the surface of myeloid cells including macrophages, monocytes, and neutrophils ( 10 ). A prior study illustrated that TREM-1 stimulated lung injury and inflammation in COPD mouse by mediating macrophage pyroptosis ( 11 ).…”
Section: Introductionmentioning
confidence: 99%